TINGKAT KEPUASAN PASIEN TERHADAP MUTU PELAYANAN FASILITAS RAWAT INAP RSUD H. ABDUL MANAP KOTA JAMBI - Pasha Aprilizi Azahra; Erna Elfrida Simanjuntak; Yeyen Gustina Irawan (Journal of Hospital Administration and Management (JHAM), 2026)
Patient satisfaction is an important indicator in assessing the quality of healthcare services provided by hospitals. This study aimed to determine the level of patient satisfaction with the quality of inpatient facility services at H. Abdul Manap Regional General Hospital, Jambi City, based on the five dimensions of Service Quality (SERVQUAL), namely tangibles, reliability, responsiveness, assurance, and empathy. This study employed a quantitative method with a descriptive research design. The study population consisted of 4,764 patients, with a sample of 98 respondents selected using an accidental sampling technique. Data were collected using a Likert-scale questionnaire and analyzed using descriptive statistics. The results showed that the overall mean score of patient satisfaction was 4.31, indicating a very satisfied category. Based on the SERVQUAL dimensions, the mean scores were 4.17 for tangibles (satisfied), 4.27 for reliability, 4.36 for responsiveness, 4.39 for assurance, and 4.36 for empathy (all categorized as very satisfied except tangibles). The assurance dimension achieved the highest mean score, while tangibles had the lowest. Overall, patients were very satisfied with the quality of inpatient facility services. Therefore, the hospital is expected to maintain its service quality while continuously improving its physical facilities to enhance patient satisfaction.